Reliability Design and Experimental Development for High-Power Electric Driving Wheel Gearbox - Zhang Lei; Zhao Juan; Zhang Bin; Li Hongbiao; Shan Hongbo; Ge Kai; Yang Bo; Li Zhaochuan; Zhang Hongtao (Jixie chuandong)
The wheel gearbox is a key component of Multi-axis super-heavy hybrid test platform,for the special nature of the application,on the one hand to meet the requirements of vehicle wheel power transmission requirements,while also meet lightweight and high reliability requirements.Therefore,in the wheel gearbox design,taking the lightweight for the wheel gearbox as the target,reliability as constraints,the optimization design scheme of the wheel gearbox is proposed.After the high- speed test,full load fatigue test and overload fatigue test verification,the wheel gearbox performance and reliability meet the requirements of super- heavy hybrid multi- axis test platform.